Control of Zn uptake in Arabidopsis halleri: a balance between Zn and Fe - Shanmugam, Varanavasiappan; Lo, Jing-Chi; Yeh, Kuo-Chen (Frontiers in Plant Science, 2013)
Zinc (Zn) is an essential plant micronutrient but is toxic in excess. To cope with excess Zn, plant species possess a strict metal homeostasis mechanism. The Zn hyperaccumulator Arabidopsis halleri has developed various adaptive mechanisms involving uptake, chelation, translocation and sequestration of Zn. In this mini review, we broadly discuss the different Zn tolerance mechanisms and then focus on controlled Zn uptake in A. halleri. Members of the ZRT/IRT-like protein (ZIP) family of metal transporters are mainly regulated by Zn and are involved in Zn uptake. A few members of the ZIP family, such as IRT1 and IRT2, are regulated by iron (Fe) and can transport multi-metals, including Zn, Fe, manganese (Mn), cadmiun (Cd) and cobalt (Co). This mini-review also discusses the differential expression of multiple metal ZIP transporters in A. halleri and A. thaliana, a non-hyperaccumulater, with Zn exposure as well as Fe deficiency and their role in controlled Zn uptake and tolerance.